12x+13=11x+5

Simple and best practice solution for 12x+13=11x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+13=11x+5 equation:


Simplifying
12x + 13 = 11x + 5

Reorder the terms:
13 + 12x = 11x + 5

Reorder the terms:
13 + 12x = 5 + 11x

Solving
13 + 12x = 5 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
13 + 12x + -11x = 5 + 11x + -11x

Combine like terms: 12x + -11x = 1x
13 + 1x = 5 + 11x + -11x

Combine like terms: 11x + -11x = 0
13 + 1x = 5 + 0
13 + 1x = 5

Add '-13' to each side of the equation.
13 + -13 + 1x = 5 + -13

Combine like terms: 13 + -13 = 0
0 + 1x = 5 + -13
1x = 5 + -13

Combine like terms: 5 + -13 = -8
1x = -8

Divide each side by '1'.
x = -8

Simplifying
x = -8

See similar equations:

| 1/4x13/2 | | 4(n-10)=2n | | 36-2x=41 | | 3400-x=8200 | | 7y/9=24 | | 36+2x=41 | | 2(1+3r)=5r | | (y^2-1)dx+6x*dy=0 | | 9u^2+0=25 | | 2/3x–5=1 | | (y^2-1)*dx+6x*dy=0 | | 25=5+0.50x | | (y^2+1)*dx+6x*dy=0 | | 20x+15y+55= | | 8v-42=5(v-3) | | -8+7k=-8(1-5k) | | 5(z+3)-2.5z=35+z+10 | | (y^2-1)*dx+6xdy=0 | | (2x-8)/(x^3-16x) | | -8(v+8)=4v-4 | | 2/3x-17 | | 6(x^2+4x+3)=0 | | X+.75x=1 | | 2z+16=66 | | A+c=940 | | n+16-45= | | 4n^2+8n+12=280 | | (x+4)(7x+5y)= | | 150m-125m+33425=35875-150m | | 15=20+3b | | 3(y+2)=4(y+3)-8 | | 9+2x=6x-3 |

Equations solver categories